Single fiber peel test to assess ultra high molecular weight polyethylene fiber mesostructure interactions. Issue 16 (5th January 2018) - McDaniel, Preston B.; Deitzel, Joseph M.; Gregory, Domenick; Polakovic, Timothy; Gillespie, John W.
ABSTRACT: In this work, a variable angle, single fiber peel test is developed to analyze the effects of fiber structure on the mixed mode failure within ultra high molecular weight polyethylene fibers. The Mode I and Mode II peel energy release rates are quantified and the effects of fiber meso/nanostructure on these modes are examined. Comparison of the load‐extension curves from the peel test with in‐situ video, and post‐mortem analysis using high‐resolution microscopy techniques indicates that Mode I and Mode II splitting are both significantly influenced by the deformation of nanoscale fibrils within a mesoscale network. The fibrils in the network are placed in tension across the peel/shear interface resulting in elevated values of peel energy release rates with an increasing number of engaged fibrils. The number of engaged fibrils is shown to increase with decreasing peel angle and increasing Mode II failure contribution. A bi‐linear mixed‐mode failure criterion is established. The results, and analysis of the fiber structure are discussed in context of their implications for load pathways in the fiber. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 46156. Abstract :